Teachers' and Students' Perceptions of Learning Atomic Structure Material Using Online Systems - Venna Tristya Nafulani; Ratu Betta Rudibyani; Emmawaty Sofya; Tasfiri Efkar (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
Teacher and Student Perceptions of Learning Atomic Structure Using Online Systems. This study aims to describe the perceptions of teachers and students towards learning the atomic structure material using an online system. The design of this study used descriptive qualitative research. The method used is a survey method with a research location at SMA Negeri 1 Tumijajar which research is conducted online through a questionnaire questionnaire by making statements in Google Forms which are distributed to teachers and students via the web. The subjects of this study consisted of 36 students of class X IPA 3 and 1 chemistry teacher. The results showed that the perceptions of teachers and students towards learning the atomic structure material, aspects of education management tend to be positive, online learning makes students more independent, students are more confident to discuss through online learning and online learning is more efficient because it can be carried out anytime and anywhere. In the aspect of human resources, it tends to be positive, online learning is able to make students and teachers develop skills and knowledge about information and communication technology (ICT) and be able to use various learning applications such as PCs and gadgets. While on the infrastructure aspect, teachers respond positively and students tend to be negative, this is because students still have problems with unstable internet access so that it can hamper the process of online learning activities